First principles insights into improved catalytic performance of BaTiO3- graphene nanocomposites in conjugation with experimental investigations. (15th August 2016) - Rastogi, Monisha; Bowen, Chris; Kushwaha, H.S.; Vaish, Rahul
Abstract: The present work aims to provide first principles insights into the catalytic performance of composites based on BaTiO3 particles decorated over reduced graphene oxide (rGO). Examination regarding the orbital contributions of valence states, conduction states, interaction surface and anchoring of perovskite over rGO have been carried out. Theoretical results thus obtained have been validated using experimental investigation. Further experiments have also been conducted to analyze the catalytic performance of composites with respect to multiple advanced oxidation processes. Charge separation has been improved due to rGO acting as macromolecular photosensitizer. Degradation of xanthene dye (Rhodamine B) and methyl orange (MO) assisted in evaluation of the catalytic performance. Acoustic irradiation provides an additional route to improve degradation by ameliorating catalytic activity (from 0.036 min to 0.099 min in RhB especially). Synergistic effect obtained through conjugated benefits of oxidation processes with proposed composite, played a crucial role in improving the overall efficiency. The cumulative outcome of the results indicates superior performance of BaTiO3 -rGO composites for green and sustainable water treatment applications.